INTEGRATION METHOD FOR MEASURING QIBLA DIRECTION (COMPARATIVE ANALYSIS OF GOOGLE EARTH AND MIZWALA) - Budiwati, Anisah; Firdaus, Muhammad Wahyu; Raharjo, Galih Cipto (Universitas Islam Indonesia, 2022)
The accuracy of measuring the qibla direction of the mosque in Kendal, Central Java, needs attention from astronomy because the majority of people only know the traditional qibla direction measurement tool namely using a compass and the sun's shadow method. Even though errors in the use of the method will result in inaccurate measurement results and have an impact on the validity of the prayers performed. Therefore, this study compares two methods that are easy for the public to use, namely Google Earth and Mizwala. Google Earth as a method to check the qibla direction and Mizwala as a comparison method to improve Google Earth. Through mathematical qualitative methods with data collection techniques through observation and interviews, it is known that these two methods are the easiest and most accurate to determine the qibla of all mosques. The method of data collection was carried out by calculating and measuring the qibla direction towards 1 mosque and 5 musholla. Although the two methods differ in terms of appearance, that Google Earth uses a satellite network while Mizwala uses the concept of the Sun's shadow, both of them can be used in an easy and integrative way. The result of Mizwala's measurements with Google Earth conclude error tolerance that is a range of minutes of angle. In the end, the two methods can be integrated to help and increase public awareness about the importance of correct qibla direction accuracy.